Odd apocalypse : an Odd Thomas novel - Koontz, Dean R. (Dean Ray), 1945- (Koontz, Dean R. (Dean Ray), 1945- Odd Thomas novel ;, 2013)
Odd Thomas confronts deadly adversaries in a decaying Hollywood estate.